2010
DOI: 10.1007/s00038-010-0181-0
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy in a population of primary health-care patients in Belgrade, Serbia

Abstract: Primary health-care patients do not have the literacy skills necessary to function adequately in the health-care environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
30
3
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 19 publications
13
30
3
5
Order By: Relevance
“…These findings were less supportive of the findings of JovicVranes et al [10] in Serbia, where the study found a very low level of job satisfaction and a generally low level of any kind of job-related satisfaction in Serbian healthcare workers. The results suggest that working conditions at all seven study sites do meet the values and aspirations of healthcare professionals.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…These findings were less supportive of the findings of JovicVranes et al [10] in Serbia, where the study found a very low level of job satisfaction and a generally low level of any kind of job-related satisfaction in Serbian healthcare workers. The results suggest that working conditions at all seven study sites do meet the values and aspirations of healthcare professionals.…”
Section: Discussioncontrasting
confidence: 93%
“…These findings are similar to those of Jovic-Vranes et al [10] in Serbia, where it was found that participants were dissatisfied with the degree of involvement of faculty clinical decisionmaking, the amount of time spent with patients and salaries. These findings slightly differ from Jain et al [10], whose results showed that dentists were significantly satisfied with theirconcern. In most cases hospital managers in the public sector have no ultimate decision-making authority on financial incentives to motivate employees to perform better.…”
Section: Factors Associated With Job Satisfactionsupporting
confidence: 89%
“…Although public health policies should provide certain preconditions for health, individuals also need to take an active role in terms of specific issues and decisions concerning health [1]. The skills required to manage our health in the best possible way also represent the essence of health literacy [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Medical and pharmaceutical researchers have increasingly focused on health literacy over the past decade, particularly as it relates to adherence with varied treatment regimens (Ngoh, 2009). Low levels of health literacy are prevalent world-wide (Jovic-Vranes, Bjegovic-Mikanovic, Marinkovic, & Kocev, 2011); inadequate health literacy is associated with poorer health outcomes, medication non-adherence, increased hospitalizations and health care costs (Eichler, Wieser, & Brugger, 2009). …”
Section: Introductionmentioning
confidence: 99%